Possibilities of Improving Wood Quality Through Breeding - Lahiri, F. A. (Indian Forester, 1959)
While carrying out the improvement of forest trees, it is very essential to bear in mind the quality of the wood that the trees will yield. The qualities which are of importance are density, strength, length and thickness of fibres, composition of wood, etc. Recent researches have shown that it is possible to breed trees, the wood of which will result in higher yield of pulp and paper. By suitable selection and breeding it is possible to breed hybrid poplars which will yield pulps of superior quality and greater yield. Strength properties also tend to increase with specific gravity. The fibril angle of species is also influenced by genetic factors. Wood of a species with small fibril angle is better than wood of the same species with a large fibril angle. The proportion of summerwood to springwood has important significance and their proportion could also be controlled by selection and breeding. The length of tracheid is also probably an inherited character, and its significance is apparent as the length of the tracheid and certain physical and mechanical properties of the wood are correlated. The grain of wood especially abnormalities like burrs, curls, spiral grain, etc., are probably hereditary and have important uses in the furniture making industries. The yield and viscosity of resin are also probably inherited characters. There are indications that the tendency to fork low may be inherited. As low forking reduces the quality of timber in a tree, this has an important bearing while raising plantations of timber-yielding trees. Modern methods of determining density, fibril-angle, etc., from increment cores of standing trees make it possible to study wood qualities, without killing them. These studies about Indian timbers should be carried out.